Modulation of the summer hydrological cycle evolution over western Europe by anthropogenic aerosols and soil‐atmosphere interactions - J. Boé (Geophysical Research Letters)
Abstract Large decadal variations in solar radiation at surface have been observed over Europe for 60 years. These variations might have impacted the hydrological cycle, through a modulation of the energy available for evapotranspiration. Here a large ensemble of climate models is analyzed to characterize the impacts of anthropogenic aerosols on the hydrological cycle over western Europe in summer and the associated uncertainties. Some models simulate strong aerosols‐driven changes in evapotranspiration and also precipitation on the historical period, while other models show virtually no impact. These opposed responses are largely determined by two seemingly independent properties of the models: the magnitude of the impact of anthropogenic aerosols on solar radiation and whether evapotranspiration is predominantly water or energy limited. Both properties, characterized on the past climate, are highly uncertain in current climate models and continue to impact the evolution of the hydrological cycle through the 21st century.